Spatial Distribution of Road Assets in Indian TOT Auctions - Shankar, Ravi; Tan, Willie (Universitas Indonesia, 2021)
In March and December 2018, the Indian government auctioned two bundles of roads to monetize its assets using the Toll-Operate-Transfer (TOT) model. This paper focuses on understanding spatial distribution of monetized road assets for TOT I and II. Our hypothesis is that there are likely to be strategic reasons for the spatial distribution. The research design consists of comparative case studies of these two auctions. The data sources include in-depth interviews with bidders, government officials, and analysts as well as documentary analyses of concession agreements, bid documents, and other secondary data. It is found that road assets for TOT I were in “politically friendly” states with better asset quality to make them bankable and encourage private participation in future auctions. The bids were well above the reserve price. For TOT II, the assets were of lower quality and three highways out of eight in the auction bundle were in left-leaning opposition-controlled states. The reserve price was also higher, and unfortunately, the bids were too low, and the contract was not awarded.